Time remaining:
H J K = J-(K-H), then -3 6 2 =

Algebra
Tutor: None Selected Time limit: 0 Hours

a.0

b.12

c.-6

d.6

e.-12

Dec 5th, 2014

6 -{[2 - (-3)}

= 6 - ( 2 +3)

= 6 -5

=1

You must have copied the question wrongly

Perhaps it is J -(K  x H)

   = 6 -[ 2 x -3]

   = 6 - (-6)

= 6 + 6 = 12    Option b


Dec 5th, 2014

Did you know? You can earn $20 for every friend you invite to Studypool!
Click here to
Refer a Friend
...
Dec 5th, 2014
...
Dec 5th, 2014
Dec 3rd, 2016
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer